INTERCULTURAL APPROACH IN TEACHING INDONESIAN LANGUAGE TO MADAGASCAR STUDENTS: COMPARATIVE STUDY BETWEEN ELEMENTARY SCHOOL AND UNIVERSITY LEARNERS - Augustin, Ravaoarisoa Simonette; Emynorane, Ralaivao Hanginiaina (Program Studi PGSD, FKIP, Universitas Mataram, 2024)
This study aims to explore the application of an intercultural approach in teaching the Indonesian language to students from Madagascar, with a comparative analysis between elementary school and university learners. The growing interest in learning Indonesian among Malagasy students, due to cultural and economic ties between Indonesia and Madagascar, presents an opportunity to examine how language acquisition can be enhanced through intercultural perspectives. Using a qualitative approach, this study uses interviews, classroom observations and document analysis to explore how Indonesian is taught in two educational contexts and how cross-cultural elements are integrated into the curriculum. The study compares different teaching methods used for elementary schools and more advanced learners at the university level, with a focus on cultural nuances, teaching strategies, and students` attitudes toward language and culture. Preliminary results suggest that while both groups benefited from the intercultural approach, the depth and complexity of intercultural content differed significantly between the two educational levels. Primary school students engage more with basic cultural concepts through interactive activities, while university students explore cultural themes more deeply through analytical discussions and educational materials. The study concluded that the intercultural approach not only enriches language learning but also promotes better cultural understanding, which is essential for improving communication skills in both contexts. This comparative study provides valuable insights into how to apply intercultural pedagogy to different age groups, offering recommendations for developing Indonesian language curriculum for Malagasy students